2015
DOI: 10.1371/journal.pone.0123975
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Detection of Cerebral Blood Flow Alterations as Assessed by Arterial Spin Labeling in Drug-Resistant Epileptic Patients

Abstract: Electrophysiological and hemodynamic data can be integrated to accurately and precisely identify the generators of abnormal electrical activity in drug-resistant focal epilepsy. Arterial Spin Labeling (ASL), a magnetic resonance imaging (MRI) technique for quantitative noninvasive measurement of cerebral blood flow (CBF), can provide a direct measure of variations in cerebral perfusion associated with the epileptic focus. In this study, we aimed to confirm the ASL diagnostic value in the identification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 71 publications
(100 reference statements)
1
47
0
Order By: Relevance
“…The quantitative CBF values were consistent with the results on normal groups obtained in a previous work [Boscolo Galazzo et al, ]. The mean CBF maps across subjects for some slices of interest are reported in Figure , along with the corresponding SD maps.…”
Section: Resultssupporting
confidence: 89%
“…The quantitative CBF values were consistent with the results on normal groups obtained in a previous work [Boscolo Galazzo et al, ]. The mean CBF maps across subjects for some slices of interest are reported in Figure , along with the corresponding SD maps.…”
Section: Resultssupporting
confidence: 89%
“…In epilepsy, the series of patients studied with ASL include mostly subjects with mesial temporal lobe epilepsy [7,8]. Overall, these studies show increased perfusion during the peri-ictal period [9][10][11][12] and decreased perfusion during the post-ictal period [9,11,13], and these findings are globally concordant with electrophysiological studies, PET and/or singlephoton emission computed tomography (SPECT). Only individual cases with neocortical epilepsy have been reported [9,11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 69%
“…Previous studies have shown increased perfusion during the periictal period, decreased perfusion during the postictal period, and hemispheric hemodynamic asymmetry in patients with epilepsy. 14,15 Thus, ASL perfusion MR imaging might help to confirm the location and extent of the EZ in the presurgical work-up of epilepsy. 16,17 Previous studies were obtained with separate PET, MR imaging, and coregistered PET/MR imaging.…”
mentioning
confidence: 99%